2022
DOI: 10.1093/mnras/stac1984
|View full text |Cite
|
Sign up to set email alerts
|

A galaxy-driven model of type Ia supernova luminosity variations

Abstract: Type Ia supernovae (SNe Ia) are used as standardisable candles to measure cosmological distances, but differences remain in their corrected luminosities which display a magnitude step as a function of host galaxy properties such as stellar mass and rest-frame U − R colour. Identifying the cause of these steps is key to cosmological analyses and provides insight into SN physics. Here we investigate the effects of SN progenitor ages on their light curve properties using a galaxy-based forward model that we compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…On the other hand, Johansson et al (2021) found a mass step that decreased in the NIR (particularly the JH bands), and that disappeared when R V was included as a free parameter in the SN Ia distance fitting, although it is possible that fitting for R V could have added noise to the distances. Additional evidence for scatter in redder SNe Ia was seen by Rose et al (2022), and evidence for correlations between host-galaxy R V variation and Hubble residuals was seen recently by Meldorf et al (2023), Kelsey et al (2023), and Wiseman et al (2022), though in these studies either a small mass step or a host-galaxy colordependent step remained after modeling the host mass-host R V relation.…”
Section: Introductionmentioning
confidence: 61%
“…On the other hand, Johansson et al (2021) found a mass step that decreased in the NIR (particularly the JH bands), and that disappeared when R V was included as a free parameter in the SN Ia distance fitting, although it is possible that fitting for R V could have added noise to the distances. Additional evidence for scatter in redder SNe Ia was seen by Rose et al (2022), and evidence for correlations between host-galaxy R V variation and Hubble residuals was seen recently by Meldorf et al (2023), Kelsey et al (2023), and Wiseman et al (2022), though in these studies either a small mass step or a host-galaxy colordependent step remained after modeling the host mass-host R V relation.…”
Section: Introductionmentioning
confidence: 61%
“…The common host properties include both the global host galaxy properties, e.g., host galaxy stellar mass, and the siblings' mean local host galaxy properties, e.g., mean SFR, mean metallicity, mean stellar age, etc. The reported correlations of SN Ia Hubble residuals with global and/or local host galaxy properties (Sullivan et al 2003(Sullivan et al , 2010Kelly et al 2010;D'Andrea et al 2011;Childress et al 2013;Rigault et al 2013Rigault et al , 2020Pan et al 2014;Uddin et al 2017;Jones et al 2018;Roman et al 2018;Rose et al 2020;Smith et al 2020;Uddin et al 2020;Johansson et al 2021;Kelsey et al 2021;Ponder et al 2021;Popovic et al 2021;Thorp et al 2021;Briday et al 2022;Meldorf et al 2023;Wiseman et al 2022) indicates σ Common > 0, or equivalently, σ Rel < σ 0 .…”
Section: σ Rel Prior Knowledgementioning
confidence: 99%
“…However, we conservatively include a systematic uncertainty in the Milky Way reddening law and analyze the data using a Cardelli et al (1989) color law. The Cardelli et al (1989) color law has the second lowest χ 2 when compared to the extinction derived from −2.5 0.0 2.5 Comparison between data and alternative simulations generated using the galaxy-driven model by Wiseman et al (2022). We compare distributions of (from top to bottom) SN x1, SN host stellar mass, SN host u − r restframe color, and correlations between x1 and host M⋆ and host u − r restframe color.…”
Section: Milky Way Extinction Correctionsmentioning
confidence: 99%
“…The DES-SN3YR sample included 207 SNe Ia from DES and was critical in the development and motivation of analyses leading up to the work presented here. This includes photometry and calibration (Burke et al 2018;Brout et al 2019b;Lasker et al 2019), survey and SN Ia population modeling (Kessler et al 2019a;Popovic et al 2021b), understanding and modeling of the 'mass/dust step' (Sullivan et al 2010a;Lampeitl et al 2010;Smith et al 2018;Scolnic et al 2020;Brout & Scolnic 2021;Popovic et al 2021a;Wiseman et al 2022;Duarte et al 2022;Dixon et al 2022;Chen et al 2022;Meldorf et al 2023), estimates and treatment of systematic uncertain-ties (Brout et al 2019a(Brout et al , 2020, and the automation of the analysis pipeline .…”
mentioning
confidence: 99%
See 1 more Smart Citation